Oxygen ultra-fine bubbles water administration prevents bone loss of glucocorticoid-induced osteoporosis in mice by suppressing osteoclast differentiation. Issue 3 (March 2017) - Noguchi, T.; Ebina, K.; Hirao, M.; Morimoto, T.; Koizumi, K.; Kitaguchi, K.; Matsuoka, H.; Iwahashi, T.; Yoshikawa, H.
Abstract Summary Oxygen ultra-fine bubbles (OUB) saline injection prevents bone loss of glucocorti-induced osteoporosis in mice, and OUB inhibit osteoclastogenesis via RANK-TRAF6-c-Fos-NFATc1 signaling and RANK-p38 MAPK signaling in vitro. Introduction Ultra-fine bubbles (<200 nm in diameter) have several unique properties, and they are tested in various medical fields. The purpose of this study was to investigate the effects of oxygen ultra-fine bubbles (OUB) on glucocorticoid-induced osteoporosis (GIO) model mice. Methods Prednisolone (PSL, 5 mg) was subcutaneously inserted in 6-month-old male C57BL/6J mice, and 200 μl of saline, OUB-diluted saline, or nitrogen ultra-fine bubbles (NUB)-diluted saline was intraperitoneally injected three times per week for 8 weeks the day after operations. Mice were divided into four groups; (1) control, sham-operation + saline; (2) GIO, PSL + saline; (3) GIO + OUB, PSL + OUB saline; (4) GIO + NUB, PSL + NUB saline. The effects of OUB on osteoblasts and osteoclasts were examined by serially diluted OUB medium in vitro. Results Bone mass was significantly decreased in GIO [bone volume/total volume (%): control vs. GIO 12.6 vs. 7.9;p < 0.01] while significantly preserved in GIO + OUB (GIO vs. GIO + OUB 7.9 vs. 12.9;p < 0.05). In addition, tartrate-resistant acid phosphatase (TRAP)-positive cells in the distal femur [mean osteoclasts number/bone surface (mm−1 )] was significantly increased in GIO (control vs. GIO 6.8 vs. 11.6;p < 0.01) while suppressed in GIO + OUB (GIO vs. GIO + OUB 11.6 vs. 7.5;p < 0.01). NUB did not affect these parameters. In vitro experiments revealed that OUB significantly inhibited osteoclastogenesis by inhibiting RANK-TRAF6-c-Fos-NFATc1 signaling, RANK-p38 MAPK signaling, and TRAP/Cathepsin K/DC-STAMP mRNA expression in a concentration-dependent manner. OUB did not affect osteoblastogenesis in vitro. Conclusions OUB prevent bone loss in GIO mice by inhibiting osteoclastogenesis.